An experimental approach to determine the critical depth of cut in brittle-to-ductile phase transition during end milling of soda lime glass - Amin, A. K. M. Nurul; Begum, Mst. Nasima; Fathiah, Noor; Konneh, Mohamed; Ariff, Tasnim Firdaus (Springer Link, 2016)
Plastic deformation is a predominant material removal mechanism in machining of ductile materials, but it is a big challenge to achieve it in cases of brittle materials. Soda-lime glass is a very useful engineering material. Due to its favorable thermal, corrosion resistance and fine chemical properties, its common applications are in the manufacture of products like mirrors, lenses, semiconductor, and optical, bio-medical and microelectronics components. Nevertheless, owing to its brittleness due to its low fracture toughness, machining of soda-lime glass is practically impossible under normal cutting conditions. Though recent investigations have shown that machining of such brittle material is possible using ductile mode machining under controlled cutting parameters and tool geometry, it remains a challenging task. This paper focuses on identification of the critical axial depth of cut under specific feed per tooth and cutting speed in high-speed end milling of soda-lime glass. A two-fluted solid end mill of 4 mm diameter was used with cutting speed ranging from 377 to 628 m/min and feed rate from 5 to 20 mm/min to investigate the phenomenon of transition from plowing to ductile and ductile to brittle machining mode. The work piece was placed at a specific angle to facilitate machining at gradual increment in depths for different feed rates and cutting speeds combinations. At the highest available cutting speed, three phases (plowing, ductile, and brittle) were observed at a specific feed rate, resulting in a critical depth of cut 51.943 μμm and chip thickness approximately 198 nm.